Blockchain in Education - Track ability and Traceability - Hashmani, M.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
Block-chain is one of the latest trends of tech world. The technology was introduced with Bitcoin and is being highly experimented for various cryptocurrencies ever since. However, with recent advancements in the technology, the research community and industries have started focusing on its applicability in other various areas such as healthcare, business, logistics, education and many more. Consequently, the research carried out in this paper investigates the use of Block-chain technology in education sector. Over the years, the use of technology in education have helped in improving the accessibility and quality of education using touch screens, Artificial Intelligence, cloud computing, e-classrooms etc. However, there are certain areas in education that need further consideration such as keeping track of students and student related records and transcripts, reduction in manual and paperwork and more. This is where Block-chain is predicted to play a significant role. In this paper, the potential applications of Block-chain for tracing and tracking in education sector are discussed. The discussion is done by first presenting the existing issues in education sector. Further, using the tracking and tracing ability of the Block-chain, few solutions to the existing problems have been proposed. The proposal of solutions is followed by the challenges of integration of Block-chain technology in education sector. Finally, the paper concludes stating that Block-chain has a huge potential in revolutionizing the education sector if the existing challenges are overcome through research and experimentation. Â© 2020 IEEE.